Differences in linear and change-of-direction speed performance between high- and low-power producers among Division II collegiate male and female soccer players when using three different methods of determining lower-body power - Lockie, R. G.; Dawes, J. J. (Journal of Australian Strength and Conditioning, 2018)
Linear and change-of-direction (COD) speed are important qualities for soccer players. Higher lower-body power should positively contribute to faster linear and COD speed specific to soccer. However, the extent to which lower-body power may contribute to these qualities could be gender-specific in collegiate soccer players and requires further investigation. Archival data from 35 Division II soccer players, which included 19 males and 16 females, was analysed. The countermovement jump (CMJ) assessed lower-body power; jump height, peak anaerobic power measured in watts (PAPw), and PAPw relative to body mass (P:BM) were calculated. Jump height provided an absolute measure of lower-body power, while PAPw and P:BM measured this capacity in relative terms. The players also completed a 30-metre (m) sprint (the 0-10 m and 0-30 m intervals were measured) to assess linear speed, and the pro-agility shuttle and T-test to evaluate COD speed. Subjects were analysed by gender, and split into high- and low-power producing groups (above or below the mean) defined by CMJ height, PAPw, and P:BM. A one-way analysis of variance (p < 0.05) compared the groups, and effect sizes (d) were also calculated. When stratified by PAPw, the high-power producing males were faster in the 0-10 m sprint interval (d = 1.25). The high-power producing males and females were faster in the 0-30 m sprint interval when defined by all power variables (d = 0.96-1.58). The high-power producing females were faster in the T-test when all power variables were used to stratify the groups (d = 1.46-1.49). Higher power in collegiate male soccer players demonstrated a significant negative relationship between linear speed but not COD speed as measured by the pro-agility shuttle and T-test.